Metabolic Conversion and Removal of Manganese Ferrite Nanoparticles in RAW264.7 Cells and Induced Alteration of Metal Transporter Gene Expression - Zhang L (Dove Medical Press, 2021)
Liang Zhang, Shilin Xiao, Xun Kang, Tao Sun, Chunyu Zhou, Zhongsheng Xu, Mengmeng Du, Ya Zhang, Guangxian Wang, Yun Liu, Dong Zhang, Mingfu Gong Department of Radiology, Xinqiao Hospital, Army Medical University, Chongqing, People’s Republic of ChinaCorrespondence: Dong Zhang; Mingfu GongDepartment of Radiology, Xinqiao Hospital, Army Medical University, No. 183, Xinqiao Street, Shapingba District, Chongqing, People’s Republic of ChinaTel +86 2368763843Fax +86 2368755306Email hszhangd@163.com; hummer198625@163.comBackground: Manganese Ferrite Nanoparticles (Mn-IONPs) are widely used in biomedical field and their cytotoxicity has been initially explored, but the mechanism remains obscure. The nano-bio interactions are believed to be crucial for cytotoxicity mechanism, while little data have been acquired.Methods: Mn-IONPs were synthesized by thermal decomposition of acetylacetonate precursor. After physicochemical characterization, we analyzed the metabolic conversion and removal of Mn-IONPs in RAW264.7 cells by Prussian blue staining, TEM, HRTEM and elemental quantitative analysis, followed by gene expression evaluation using quantitative RT-PCR.Results: Mn-IONPs were successfully synthesized. Both the uptake and cytotoxicity of Mn-IONPs on RAW264.7 cells were time- and dose-dependent. After internalized, Mn-IONPs were passed to daughter cells with passages on. Meanwhile, Mn-IONPs were exocytosed and digested to metal ions and further excreted out, resulted in the labeling rate and ions contents decreased gradually. As ion influx related genes, the expressions of ZIP14, IRP2, FtH and DMT1 were suppressed within 24 hours but overexpressed to a plateau at the 48th hour in a dose-dependent manner. At the 72nd hour, ZIP14 and DMT1 mRNA levels decreased toward normal, while IRP2 and FtH kept up-regulated. As efflux related genes, FPN, SLC30A10 and Hamp2 genes were up-regulated within 24– 72 hours; SPCA1 was suppressed at the 24th and 72nd hour, while overexpressed at the 48th hour. All the efflux related genes’ mRNA had a dose-dependent increasing manner at the corresponding time points.Conclusion: Mn-IONPs showed time- and dose-dependent cytotoxicity and cell labeling rate in RAW264.7 cells. Accompanying with the intracellular catabolic breakdown and exocytosis of Mn-IONPs, RAW264.7 cells also secreted and re-uptook manganese and iron ions to maintain intracellular homeostasis in the succeeding passages. And the metabolic conversion of Mn-IONPs in RAW264.7 cells can affect the expression of ZIP14, DMT1, FPN, SLC30A10, IRP2, FtH, Hamp2 and SPCA1 genes.Keywords: manganese ferrite nanoparticles, cytotoxicity, metabolism, metal transporter genes, RAW264.7 macrophage cells